Efisiensi dan produktivitas industri perbankan pada sistem moneter ganda di Indonesia - Aam Slamet Rusydiana; Nisful Laila; Sudana Sudana (Jurnal Siasat Bisnis, 2019)
This study aims to examine the level of efficiency of 115 commercial banks in Indonesia for the period between 2010 and 2016. We use basic models of Data Envelopment Analysis (DEA) consisting of CCR (Charnes Cooper Rhodes) and BCC (Banker Charnes Cooper) models. This study also investigate the value of productivity of each bank which is then compared. The study finds that commercial banks in Indonesia exhibit an increase in productivity although it is relatively small. The stagnation of the level of productivity is due to the low level of technological change (technological change) rather than a decrease in efficiency (Efficiency change). Another interesting finding is that around 70 percent of the hypothetically relative credit market share in Indonesia is controlled by only 29.56 percent of commercial banks. This also means that around 30 percent of the remaining credit market share is contested by the rest of other banks.